Effect of helium incorporation on plasma parameters and characteristic properties of hydrogen free carbon films deposited using DC magnetron sputtering - Bibhuti B. Sahu (2020)
© 2020 Author(s). The present work investigates the effects of helium (He) gas mixing with Ar on plasma parameters and examines its effect on film properties of C films. We used a closed-field unbalanced magnetron sputtering system for the deposition of C thin films at a direct current power density of 30 W/cm2 and an operating pressure of ≈3 mTorr. On the basis of systematic analysis, we present an attempt to enhance the electron temperature and investigate the high-energy electron tail, which is required for the efficient ionization in the plasmas, by incorporating He gas in the Ar background. This approach also promotes the plasma density to become high, which is more than two times at a mixing ratio of 80%. Moreover, the present study utilizes these plasma conditions to prepare hydrogen-free highly conductive nanostructured carbon films. Systematic plasma diagnostic and film analysis reveal that a high content of He incorporation is accountable for the fabrication of a highly conductive nanocrystalline carbon film in a high-density plasma environment.